B Cell Dysfunction Associated With Aging and Autoimmune Diseases - Ma, Shiliang; Wang, Chengwei; Mao, Xinru; Hao, Yi (Frontiers in Immunology, 2019)
Impaired humoral responses, as well as an increased propensity for autoimmunity, play an important role in the development of immune system dysfunction associated with aging. Accumulation of a subset of atypical B cells, termed age-associated B cells (ABCs), is one of the key age-related changes in B cell compartments. ABCs are characterized by their distinct phenotypes, gene expression profiles, special survival requirements, variations in B cell receptor repertoires and unique functions. Here, we summarize recent progress in the knowledge base related to the features of ABCs, their potential role in immune senescence, and their relationship with autoimmune diseases.